Summed dominance ratio-based analysis of weed diversity and dominance in maize fields - Kansa Dianti Putri; Mutmainnah; Kiky Nurfitri Sari; Indriati Meilina Sari; Andika Prawanto (Journal of Agrosociology and Sustainability, 2026)
Background: Maize (Zea mays L.) is an important food crop in Indonesia, but its productivity is frequently reduced by weed competition for essential growth resources. Weed composition and dominance vary with environmental and management conditions, highlighting the need for site-specific weed management. Understanding local weed communities is also important for developing sustainable weed control strategies that minimize environmental impacts while maintaining crop productivity. Therefore, this study aimed to characterize weed communities in maize fields across three locations in Rejang Lebong Regency by analyzing species composition, dominance structure using SDR, ecological interpretation, community similarity using the Community Coefficient (CC) analysis, and their implications for weed management, including potential allelopathic profiles of dominant weed species. Methods: The study was conducted in December 2025 using a 1 x 1 m quadrat method in three maize fields, with three sampling plots created at each location (n = 9 quadrats). Weed dominance was measured using density, frequency, the Importance Value Index (IVI), and the Summed Dominance Ratio (SDR), whereas community resemblance was assessed using the CC. Findings: A total of 16 weed species were found across the study areas. Ageratum conyzoides dominated Locations 1 and 2, with SDR values of 28.53% and 34.85%, respectively, whereas Bidens pilosa (22.00%) and Setaria barbata (21.39%) co-dominated Location 3. Broadleaf weeds were the most common functional group across all locales. Community resemblance between locations was low (CC = 29.28-48.47%), indicating diverse weed communities. Conclusion: Maize fields in Rejang Lebong were dominated by 16 weed species, with strong single-species dominance by Ageratum conyzoides (SDR up to 34.85%) at some sites, while Community Coefficient values below 75% indicated non-homogeneous weed communities among locations. These findings provide a quantitative baseline for regional weed management and highlight the importance of integrated, site-specific approaches that combine mechanical weeding, crop rotation, mulching, and selective herbicide use to improve weed control efficiency, reduce unnecessary herbicide inputs, and support sustainable maize production. Novelty/Originality of this article: This study demonstrates how integrating SDR and CC analyses improves the identification of dominant weed species and community variation, providing scientific evidence for site-specific weed management and more sustainable maize production.